Design of Single-Phase-to-Three-Phase System Reconfiguration to Improve Voltage and Increase kWh Sales Potential on the BF05K2039 Low-Voltage Overhead Distribution Network, Feeder C, ULP Sei Duri - M. Fajri Nugroho; Dedi Nugroho (Journal of Engineering, Electrical and Informatics, 2026)
Voltage quality in a low-voltage distribution network determines both the quality of electricity received by customers and distribution efficiency. At the BF05K2039 Distribution Transformer, Feeder C, ULP Sei Duri, far-end customers experienced low voltage because the existing network still used a single-phase configuration with NFA2X-T 2×10 mm² conductors. This study evaluates the before-and-after performance of reconfiguring the network into a three-phase system and uprating the main conductor to NFA2X-T 3×70+1×70 mm², focusing on the voltage profile, voltage drop, and calculated power losses. A quantitative case-study approach was employed, consisting of field measurements at 20 customer points, calculation of the initial condition, implementation of the reconfiguration design, and post-work remeasurement. Customer voltages increased from 210–226 V to 233–238 V, while the far-end voltage difference from the source decreased from approximately 26 V (11%) to about 4 V (2.2%). Using the study's simplified calculation method, estimated power losses decreased from 1,755.30 W to 152.46 W, a difference of 1,602.84 W. Under the analytical assumptions of 720 operating hours per month and IDR 750/kWh, this difference corresponds to an estimated 1,154.045 kWh per month and an indicative monetary equivalent of approximately IDR 865,534 per month. These kWh and monetary figures are engineering estimates derived from the calculated loss difference, not direct measurements of additional billed energy, realized revenue, or investment return.